Place, pedagogy and play : participation, design and research with children - Khan, Matluba; Bell, Simon, 1957 May 24-; Wood, Jenny, 1991-; Researching With and For Children: Place, Pedagogy and Play (Conference) (2017 : University of Edinburgh) (New York : Routledge, 2021)
"Place, Pedagogy and Play connects landscape architecture with education, psychology, public health and planning. Over the course of thirteen chapters it examines how design and research of places can be looked into from multiple lenses, that of pedagogy and play and how children, as competent social agents, are engaged in the process of designing their own spaces, and brings a global perspective to the debate around child friendly environments. Despite growing evidence of the benefits of nature for health, well-being, play and learning, children are increasingly spending more time indoors. Indeed, new policy ideas and public campaigns suggest how children can become better-connected with nature, yet linking outdoor space to pedagogy is largely overlooked in research. By focusing on three themes within these debates, place and play; place and pedagogy; and place and participation, this book explores a variety of angles to show that best practice requires dialogue between research disciplines, designers, educationists and psychologists, and a move beyond seeing the spaces children inhabit as the domain only of childhood professionals. Through illustrated case studies it presents a wider picture of the state of childhood today, and offers practical solutions and further research avenues that promote a more holistic and internationally focused perspective on place, pedagogy and play for built environment professionals"--
Manufactured play equipment or loose parts? : examining the relationship between play materials and young children's creative play / Reyhaneh Mozaffar, Napier University -- Becoming naturish: ways of coming to know nature in the primary school / Cathy Francis, University of Aberdeen -- A view from China : reflecting on the participation of children and young people in urban planning / Yupeng Ren, Yantai University.
Includes bibliographical references and index.
Keywords: Children and the environment; Play environments; Place-based education